Dual threat: Susceptibility mechanisms and treatment strategies for COVID-19 and bacterial co-infections - Keda Chen; Ruiqi Weng; Jiaxuan Li; Hao Wu; Xiaotian Tie; Hongyu Li; Yuanyuan Zhang (Computational and Structural Biotechnology Journal)
COVID-19 has rapidly spread worldwide, posing significant challenges to public health systems. This review offers an in-depth examination of the mechanisms underlying susceptibility and associated clinical features, and treatment strategies associated with bacterial co-infections in COVID-19 patients. A structured review of the literature revealed that the overall rate of bacterial co-infection among COVID-19 patients is relatively low (6.9 %). However, the rate increases significantly in severe cases (8.1 %) and reaches as high as 23.5 % among ICU patients. Common pathogens include Staphylococcus aureus, Streptococcus pneumoniae, and Klebsiella species. These co-infections contribute to increased disease severity, complicate treatment, and elevate the risk of mortality. Meanwhile, the widespread use of antibiotics has further intensified antimicrobial resistance. In terms of clinical management, we propose the ''Four Antis and Two Balances'' approach, which includes antiviral therapy, anti-shock treatment, prevention of hypoxia, control of secondary infections, as well as maintaining electrolyte/acid-base balance and microecological stability. Emerging therapeutic strategies include antiviral agents, immunomodulators, artificial liver support systems, and cell-based therapies. Public health policy recommendations focus on antimicrobial stewardship programs, biomarker-guided antibiotic use, and investment in rapid diagnostic technologies. Elucidating the immunological, cellular, and molecular mechanisms underlying these interactions will be essential for advancing more targeted intervention strategies. This review provides evidence-based guidance for clinicians in the management of COVID-19 cases complicated by bacterial co-infections, and provides valuable insights for public health policy in addressing the dual challenge of COVID-19 and antimicrobial resistance.